2017
DOI: 10.1097/tp.0000000000001666
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Waitlist Mortality in Portopulmonary Hypertension

Abstract: Background The current Organ Procurement Transplantation Network (OPTN) policy grants Model for End Stage Liver Disease (MELD) exception points to patients with portopulmonary hypertension (POPH), but potentially important factors, such as severity of liver disease and pulmonary hypertension, are not included in the exception score, and may affect survival. The purpose of this study was to identify significant predictors of waitlist mortality in patients with POPH. Methods We performed a retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 26 publications
0
69
0
4
Order By: Relevance
“…This hemodynamic target for liver transplantation fluctuates among the institutions based on their multidisciplinary evaluation, comorbidities, inclusion of PVR in the hemodynamic evaluation, and prior experiences with similar patients. Although predictors of waitlist mortality exist, i.e., PVR and Model for End‐stage Liver Disease (MELD) score, there are no clear predictors of treatment response. Until prospective studies address this issue, it may be prudent to use intravenous prostacyclin analogues and or combination therapies in the most severe cases of PoPH, especially if liver transplantation is to be considered .…”
Section: Impact Of Pah‐specific Therapies On Liver Transplantation Elmentioning
confidence: 99%
See 1 more Smart Citation
“…This hemodynamic target for liver transplantation fluctuates among the institutions based on their multidisciplinary evaluation, comorbidities, inclusion of PVR in the hemodynamic evaluation, and prior experiences with similar patients. Although predictors of waitlist mortality exist, i.e., PVR and Model for End‐stage Liver Disease (MELD) score, there are no clear predictors of treatment response. Until prospective studies address this issue, it may be prudent to use intravenous prostacyclin analogues and or combination therapies in the most severe cases of PoPH, especially if liver transplantation is to be considered .…”
Section: Impact Of Pah‐specific Therapies On Liver Transplantation Elmentioning
confidence: 99%
“…Variable criteria to offer or deny liver transplantation among liver transplant teams and regional review boards b. Restrictive criteria to obtain MELD exception points based on PoPH (94) c. Not appreciating or recognizing the positive treatment effect on PVR, cardiac output, and right ventricular function when minimal changes in mPAP occur (23) d. Limited studies documenting dose reduction or discontinuation of PAH-specific therapies post-liver transplant with biliary cirrhosis, bosentan decreased the portal pressure by reducing the hepatocollateral vascular resistance. (75) In a mouse model of cirrhosis, chronic administration of endothelin receptor antagonists caused a reduction in liver fibrosis and portal pressure.…”
Section: Effect Of Pah-specific Medications On Portal Hypertensionmentioning
confidence: 99%
“…It is not yet clear which patients are most likely to benefit from LT. A retrospective analysis of a French registry showed that PH was normalized in the majority (60,9%) of patients undergoing LT, but those characteristics predicting a favorable outcome remain to be identified [127]. Both the severity of liver disease and PoPH are significantly associated with waitlist, but not post-transplant mortality [128]. Available data regarding the association between PAP and survival rates after LT in patients with PoPH show a 100% mortality rate for patients with mean PAP >50 mmHg, 50% for mean PAP <50 mmHg and >35 mmHg, and 0% for mean PAP <35 mmHg [129].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…26 For those with MELD score >15 and baseline PVR >450 dyne/s/cm 5 , wait-list mortality is increased, but transplant risk appears to lessen if mPAP can be decreased to <35 mm Hg with acceptable right ventricle function. 27 The latter parameter is perhaps the most important and in need of further study. Edwards 61 POPH autopsy series describing "plexogenic arteriopathy" 1990…”
Section: Portopulmonary Hypertensionmentioning
confidence: 99%